Factors affecting quality of life of caregivers of children diagnosed with autism spectrum disorder - Ozgur, Borte; Aksu, Hatice; Eser, Erhan (Indian journal of psychiatry, 2018)
Context: Since autism spectrum disorder (ASD) is a lifelong disease and because of its nature, the negative effects of the disease on the quality of life (QoL) of caregivers as well as patients are incontrovertible. Aims: It was aimed to evaluate the effect of the variables related to both parents and children on the QoL scores of the parents of the children with ASD. Settings and Design: This is a causality analysis study. Subjects and Methods: Questionnaire on sociodemographic/disease-related variables, QoL in Autism Questionnaire-Parent Version (QoLA-P), autism behavior checklist and Clinical Global Impression scale were assessed of 162 patients with ASD. Statistical Analysis Used: Unpaired t- test, Mann-Whitney U test, Kruskal-Wallis test, and one-way ANOVA test were used for comparing groups. The parameters found to be statistically significant for QoLA-P in different analyses were included as the independent variable in the logistic regression analysis. The backward (variable elimination) model was selected as the model in the analysis. Results: The causality has been established may be stated as the severity of autism, the presence of psychiatric disorder in the mother/father, attendance of the child at school, duration since the diagnosis of autism, and the child's medication use. Conclusions: Autism affects the QoL of caregivers. The intervention of treatment by considering the factors that affect the QoL positively or negatively may increase the QoL of caregivers.